Non-aqueous dual-carbon lithium-ion capacitors: a review. Issue 26 (21st June 2019) - Li, Guangchao; Yang, Zhewei; Yin, Zhoulan; Guo, Huajun; Wang, Zhixing; Yan, Guochun; Liu, Yong; Li, Lingjun; Wang, Jiexi
Abstract : Lithium-ion capacitors have attracted tremendous attention among various electrochemical energy storage systems, benefitting from the merits of high energy density, high power output, long cycle life and favorable chemical stability. Abstract : By reducing the gap between lithium-ion batteries (LIBs) and supercapacitors (SCs) effectively, lithium-ion capacitors (LICs) have attracted tremendous attention among various electrochemical energy storage systems because they exhibit a high energy density (inherited from the LIBs), a high power output, long lifespan (owing to the SCs) and favorable chemical stability. Carbonaceous electrode materials play significant roles in high performance dual-carbon LICs whether positive or negative. Here, the working mechanism, cell design principle and recent progress in carbon-based electrode materials for dual-carbon LICs are illustrated. Then, the commercialization of LICs is discussed briefly. Finally, some suggestions for the future developments associated with dual-carbon LICs are proposed.